Interface behavior and tensile properties of Mg-14Li-3Al-2Gd sheets prepared by four-layer accumulative roll bonding. (January 2021) - Wei, Zhen; Zheng, Haipeng; Wu, Ruizhi; Zhang, Jinghuai; Wu, Huajie; Jin, Siyuan; Jiao, Yunlei; Hou, Legan
Abstract: Mg-14Li-3Al-2Gd sheets were prepared by four-layer accumulative roll bonding (ARB) with two-step rolling in one cycle. The interface behavior of Mg-14Li-3Al-2Gd sheets was investigated, and the fracture morphology and mechanical properties of the alloy sheets were analyzed. Results show that, the number of grains in the direction of normal direction of the single-layer decreases rapidly and the grain size decreases gradually in the ARB process. With the increase of the ARB cycle, the microstructure evolution transits from single-layer evolution to multi-layer evolution gradually. Meanwhile, the strength, interfacial bond strength increases and plasticity decreases constantly.